Peningkatan Kompetensi Kewirausahaan Siswa SMK Melalui Pelatihan Penyusunan Business Model Canvas Berbasis Digital - Elvi Rahmi; Efni Cerya; Friyatmi Friyatmi (Universitas Negeri Padang, 2020)
This article aims to describe how the entrepreneurial competence of vocational school students after being given training in compiling a business plan using the Business Model Canvas. The Business Model Canvas is a comprehensive yet practical business model. This article uses a descriptive method, because this research is not intended to test certain hypotheses but only describes